Expanding Repertoire In The Oculomotor Periphery: Selective Compartmental Function In Rectus Extraocular Muscles - Demer, Joseph L. (2011)
Since connective tissue pulleys implement Listing's law by systematically changing rectus extraocular muscle (EOM) pulling directions, non-Listing's law gaze-dependence of the vestibulo-ocular reflex is currently inexplicable. Differential activation of compartments within rectus EOMs may endow the ocular motor system with more behavioral diversity than previously supposed. Innervation to horizontal, but not vertical, rectus EOMs of mammals is segregated into superior and inferior compartments. Magnetic resonance imaging in normal subjects demonstrates contractile changes in the lateral rectus (LR) inferior, but not superior, compartment during ocular counter-rolling (OCR) induced by head tilt. In human orbits ipsilesional to unilateral superior oblique palsy, neither LR compartment exhibits contractile change during head tilt, although the inferior compartment contracts normally in contralesional orbits. This suggests that differential compartmental LR contraction assists normal OCR. Computational simulation suggests that differential compartmental action in horizontal rectus EOMs could achieve more force than required by vertical fusional vergence.